1982
DOI: 10.1288/00005537-198204000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years experience with intranasal transseptal dacryocystorhinostomy

Abstract: The intranasal transeptal approach for treating chronic dacryocystitis has been utilized by the authors since 1959. A total of 305 operations have been performed with a high success rate and very low complication rate. The intranasal approach is preferred since it allows good visualization of the lacrimal sac, avoids a facial scar, and is most successful. Two hundred and eighty-four primary operations were performed with an 89% success. Of 29 failures, 25 were re-operated on with only 2 failures. Counting pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The intranasal approach was widely attempted in the field of otolaryngology until the 1980s, and the success rate has been reported to be 80-90%, which is comparable to the skin approach 8,9. Nevertheless, the intranasal approach has not been established as the mainstream modality.…”
Section: Discussionmentioning
confidence: 99%
“…The intranasal approach was widely attempted in the field of otolaryngology until the 1980s, and the success rate has been reported to be 80-90%, which is comparable to the skin approach 8,9. Nevertheless, the intranasal approach has not been established as the mainstream modality.…”
Section: Discussionmentioning
confidence: 99%
“…Nayak et al, 1999. 16 In a study by Berryhill BH, Dorenbusch AA ; they found that in their series, Two hundred and eighty-four primary operations were performed with an 89% success. Of 29 failures, 25 were reoperated on with only 2 failures.…”
Section: Objective Assessmentmentioning
confidence: 99%